HUKUM ALIH FUNGSI HARTA WAKAF PRODUKTIF UNTUK KEGUNAAN KOMERSIAL DALAM PRESPEKTIF FIQIH MUAMALAH - Bukhori Bukhori (Mutawasith: Jurnal Hukum Islam, 2018)
The legal phenomenon of the function of a productive Waqf property is seen from the problem of changing the spatial policy of an area, the exclusion of the function of the Waqf land switch. This research aims to determine the purpose of the law over the function of the Waqf of commercial use in the presence of the Muamalah; The possibility or absence of a switch of the Waqf property in the use of Kmersil in Islamic view or in the regulation of the Government of Indonesia. The method used in this paper is the library research method. Types of approaches used are qualitative descriptive. The results concluded that Waqf as a means of realizing social welfare and the capital in the development and progress of Islam. Analysis of the transfer of productive Waqf property in the fiqh of the jurisprudence, some scholars argue: Abu Hanafiyah, Malikiyah and Hanabillah allow the transfer of Waqf of productive property for commercial use with the conditions being removed Enable only a few and not change the status. It does not eliminate the existence of the place or should be exchanged with other places and the process over the function should be the element of Maslahah. Meanwhile, according to) the Madhhab Imam Syafi'iyah Prohibition of the transfer of Waqf property productive because the property of the Waqf is eternal and has become the property of Allah and return to Allah SWT.